Studies on the Mechanism of Action of Synthetic Antifibrinolytics - Landmann, H (Thrombosis and Haemostasis, 1973)
When compared with derivatives of benzamidine, the synthetic antifibrinolytics EACA, PAMBA, and trans-AMCHA are weak competitive inhibitors of ester hydrolysis by urokinase, of plasminogen activation by urokinase and streptokinase, and of plasmin action on synthetic substrates, casein, and fibrinogen. In contrast, the inhibitory effect of the antifibrinolytics equal or surpass, that of benzamidine derivatives on the process of fibrin dissolution by plasmin and on plasma clot lysis. Degradation of fibrin monomers by plasmin seems to be equally strongly inhibited by the antifibrinolytics. Thus, fibrin and fibrin monomers are plasmin substrates, the hydrolysis of which is inhibited by the antifibrinolytics in a different way from their other inhibitory effects on plasmin. It is concluded that this activity accounts for the strong action of these inhibitors on the whole process of fibrinolysis.Plasmin, in contrast to other proteolytic enzymes, was shown to possess a specific ability to attack fibrin resulting in rapid formation of soluble products from the insoluble substrate. The strong inhibitory effect of the antifibrinolytics is not caused by their reaction with the substrate, fibrin, but by their blocking the specific interaction of plasmin with fibrin.The molecular mechanism of the plasmin-fibrin reaction and its inhibition is discussed.